PEMAHAMAN TEOLOGIS TENTANG KEHIDUPAN DOA DAN MENARA DOA - Rumaijuk, Stefan (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
The life of prayer is a responsibility to set aside time to pray, to be disciplined in building a relationship with God, to have self-submission and reverence toward God, and to make prayer a necessity. Meanwhile, a prayer tower is an activity of prayer, praise, and worship that has taken place and is currently ongoing. The Tabernacle of David is a representation of the prayer tower in the Old Testament era, while the Upper Room is a representation of the prayer tower in the New Testament era. As believers, we need to correctly understand the theological foundations of the prayer tower, so that we do not misapply it in our Christian lives. The prayer tower is a crucial element in the harvesting of souls in these end times and serves as a trigger to help us participate in fulfilling the Great Commission of the Lord Jesus.